2005
DOI: 10.1111/j.0001-6349.2005.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking and causes of very preterm birth

Abstract: Smoking increases the risk of very preterm birth caused by preterm labor (including idiopathic preterm labor), preterm premature rupture of membranes, and late pregnancy bleedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 21 publications
5
54
0
1
Order By: Relevance
“…However, as expected, we found that maternal smoking and history of PTB were the main risk factors for PTB in cases. This is in accordance with the present literature [3,5,16,17,20,25]. Conversely, bacterial vaginosis and LLETZ conisation were not associated with PTB in our study, although they represent established risk factors for PTB.…”
Section: Discussionsupporting
confidence: 93%
“…However, as expected, we found that maternal smoking and history of PTB were the main risk factors for PTB in cases. This is in accordance with the present literature [3,5,16,17,20,25]. Conversely, bacterial vaginosis and LLETZ conisation were not associated with PTB in our study, although they represent established risk factors for PTB.…”
Section: Discussionsupporting
confidence: 93%
“…Theories on how smoking causes ectopic pregnancy include fallopian tube ciliary damage causing decreased ovum transit times and inflammation interfering with fertilization. 21 Like other studies in the literature, this study found that smokers have a higher incidence of poor pregnancy outcomes, including PPROM, 20,22 preterm labor, 22,23 placental abruption, 20,24 IUGR, 25,26 and intrauterine fetal demise. 27,28 There are several limitations to this study.…”
Section: Discussionsupporting
confidence: 76%
“…Very preterm infants (24-31 weeks) had an overall prevalence of birth defects 2.3 times that of moderately preterm infants (32-36 weeks). This gradient might have occurred because some factors such as maternal smoking and diabetes that increase the risk of very preterm birth are also related to the risk of certain birth defects [13,14]. The ascertainment of birth defects also depends on the thoroughness and training of the examiner [15].…”
Section: Discussionmentioning
confidence: 99%
“…Stratified analysis was used to assess factors potentially modifying the association between preterm birth and birth defects. Factors assessed included: maternal race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, other), maternal age in years (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), C35) number of previous live births (none, 1 or more), maternal education (\12 years, 12 years, [12 years), initiation of prenatal care (first trimester, second trimester, third trimester, no prenatal care), and delivery method (vaginal, vaginal birth after C-section, primary C-section, repeat C-section). To improve comparability, birth certificates were used as the source of these data for both the numerator and denominator.…”
Section: Methodsmentioning
confidence: 99%